Sex Work and the Karmic Wheel: How Buddhism Influences Sex Work in China - Tsang, Eileen Yuk-Ha (International journal of offender therapy and comparative criminology, 2019)
As prostitution is widely condemned as a form of criminality in China, there is a need to examine how Buddhism functions not as a form of therapy for the purposes of rehabilitating or deterring prostitution but as a force that encourages participation in prostitution. In this work, we argue that rural-urban migrant sex workers who are Buddhists appropriate the religion's teachings of compassion, mindfulness, and karma to find a renewed sense of meaning and purpose in their livelihoods. We illustrate how Buddhism allows sex workers to cultivate the affective labor required for the purposes of servicing male clients in conjunction with finding positive purpose in their lives. In doing so, their bodies gain affirmative value in the form of helping their heterosexual male clients address deficits in their masculinities.